The role of biological agents in the management of large vessel vasculitis (LVV): a systematic review and meta-analysis. - Mohammed Osman; Christian Pagnoux; Donna M Dryden; Dale Storie; Elaine Yacyshyn (PLoS ONE)
Background Giant cell arteritis (GCA) and Takayasu's arteritis (TAA) are large vessel vasculitides (LVV) for which corticosteroids (CS) are the mainstay for treatment. In patients with LVV unable to tolerate CS, biological agents have been used with variable effectiveness. Objective To systematically review the effectiveness and safety of biological agents in patients with LVV. Methods We searched 5 electronic databases (inception to October 2012) and conference abstracts with no language restrictions. Two reviewers independently selected studies, extracted data and assessed methodological quality. Our protocol was registered in PROSPERO. Results We included 25 studies (3 RCTs and 22 case series with ≥2 cases). 95 GCA and 98 TAA patients received biological agents. The RCTs using anti-TNF agents (infliximab, etanercept and adalimumab) did not suggest a benefit in GCA. GCA patients receiving tocilizumab, in case series, achieved remission (19 patients) and reduction of corticosteroid dose (mean difference, -16.55 mg/day (95% CI: -26.24, -6.86)). In case series, 75 patients with refractory TAA treated with infliximab discontinued CS 32% of the time. Remission was variably defined and the studies were clinically heterogeneous which precluded further analysis. Conclusion This systematic review demonstrated a weak evidence base on which to assess the effectiveness of biological treatment in LVV. Evidence from RCTs suggests that anti-TNF agents are not effective for remission or reduction of CS use. Tocilizumab and infliximab may be effective in the management of LVV and refractory TAA, respectively, although the evidence comes from case series. Future analytical studies are needed to confirm these findings.